2020
DOI: 10.3390/nu12113468
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dietary Habits, Food Attitudes and Food Security Status among Adults Living within the United States Three Months Post-Mandated Quarantine: A Cross-Sectional Study

Abstract: COVID-19 has disrupted the lives of many and may have influenced dietary habits through factors such as food security status and attitudes. The purpose of this study was to identify dietary habits and their associations with food insecurity and attitudes among adults living in the United States within three months post-mandated quarantine. An online cross-sectional study was conducted from April to June 2020. Participants (n = 3133) responded to a 71-item questionnaire regarding demographics (n = 7), health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 33 publications
7
83
0
6
Order By: Relevance
“…The small changes in diet, alcohol, and smoking habits in the present study are in line with studies from other countries [ 10 , 11 , 12 , 13 , 15 , 17 , 19 ]. However, perceived changes varied between and within subgroups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The small changes in diet, alcohol, and smoking habits in the present study are in line with studies from other countries [ 10 , 11 , 12 , 13 , 15 , 17 , 19 ]. However, perceived changes varied between and within subgroups.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, in Italy, total PA decreased significantly during the first COVID-19 wave as compared to before, in all age groups and especially in men [ 9 ]. Moreover, several studies have shown small changes in dietary habits [ 10 , 11 , 12 ], while others have reported an increase in unhealthy food intake, overeating, and snacking between meals [ 10 , 13 , 14 , 15 ]. Similarly, studies have indicated that alcohol consumption has not changed during home confinement [ 13 , 16 ], while others have reported increased alcohol consumption [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they were also more likely to report increasing their canned fruit and vegetable consumption compared with food-secure respondents. These findings are consistent with other studies that have found increases in the consumption of shelf-stable foods and decreases in that of fresh foods since the beginning of the COVID-19 pandemic [35,36,[44][45][46][47]. Several studies have also found that a higher proportion of food-insecure individuals report buying less fresh foods [35,36].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have examined changes in fruit and vegetable consumption since the beginning of the COVID-19 pandemic. In a nationwide study of U.S. adults, 28.2% reported consuming less non-starchy vegetables, and 33.4% reported decreased consumption of fruit [44]. Two studies in Italy focused specifically on change in fresh fruit and vegetable intake: in one study, 18% of the respondents reported consuming less fresh vegetables, and about 17% reported consuming less fresh fruit, while in the other study 8.7% of the respondents reported consuming less fresh fruits and vegetables [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we did not collect information on the educational or socioeconomic level of participants. Many of the cross-sectional studies conducted during the pandemic aimed to analyze modifications in health-related behaviors [8,9,33,[51][52][53] report an over representation of higher educated people, and in many cases, younger age groups are overrepresented as well. In our study, we cannot assess the potential unequal distribution regarding the level of education.…”
Section: Discussionmentioning
confidence: 99%